Penerapan Model Pembelajaran Problem Based Learning Berbantuan Buku Ajar Dalam Meningkatkan Hasil Belajar Akuntansi Perbankan Syariah - Hanifah Rahma Fadilah; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Efforts that can be made to improve learning outcomes are to use learning models that can be considered suitable for improving learning outcomes, one of the most widely used learning models is Problem Based Learning (PBL). The research is used as a tool for analyzing the learning outcomes of Problem Based Learning (PBL), for analyzing the activities carried out by the teacher during the learning process, for evaluating student activities during the teaching and learning process in the classroom or outside the classroom, as well as for analyzing student responses after carrying out learning activities using learning model Problem Based Learning (PBL). The type of research chosen was a Classroom Action Research method or PTK focused on the research model conducted by Kemmis and Mc Taggart. The subjects of this study were XI Sharia Banking (PBS) students of SMK Negeri 1 Sambeng for the 2019/2020 academic period with 30 students. The results conveyed that the teacher had made Problem Based Learning (PBL) according to the syntax stated in the Learning Implementation Plan or abbreviated as RPP which was proven by an increase in student scores and a good response from students.